Design of RCS Reduction Applied to W-Band Circularly Polarized Antenna Array - Chun-Hong Chen; Pei-Yang Wang; Jun Chen; Ting Xu (International Journal of Antennas and Propagation)
A single-layer capsule-shaped polarization conversion metasurface (PCM) is proposed in this paper. In the W-band, its polarization conversion rate (PCR) exceeds 97%, effectively changing the polarization direction of the incident wave. PCM is arranged in a chessboard array to achieve broadband RCS reduction. Placing the PCM array on a circularly polarized sequentially rotated slot antenna array, simulated results show that the radiation characteristics of the antenna array are hardly affected by the PCM array. The results of measurement demonstrate that the RCS of the antenna array with PCM array proposed is reduced by more than 10 dB from 40 to 119 GHz; the relative bandwidth (−10 dB) reaches 96.3%.